Statistical process monitoring using advanced data-driven and deep learning approaches : theory and practical applications /: theory and practical applications. (2020) - Harrou, Fouzi; Sun, Ying; Hering, Amanda S; Madakyaru, Muddu; Dairi, Abdelkader
No abstract available